ALGORITMA OPTIMISASI WHALE UNTUK DIAGNOSTIK MEDIS: REVIEW LITERATUR SECARA SISTEMATIS - Septian, Firza; Utami, Ema (Universitas Lembah Dempo, 2022)
A lot of factors, including noise, have a harmful impact on the health of people from all walks of life, including unborn children. In the medical field, grouping research utilizing WOA was required. Data is gathered from a number of reliable sources, including IEEE and Scopus. Practical applications serve as a